Pengaruh Kinerja Keuangan, Keberagaman Gender, dan Environmental, Social, and Governance (ESG) terhadap Nilai Perusahaan : Studi Kasus Perusahaan yang Terdaftar di Indeks LQ45 Periode 2021–2024 - Ilham Apta Triswanda; Zaenal Abidin (Lembaga Pengembangan Kinerja Dosen, 2026)
One of the places to invest is the capital market, which is facilitated by the Indonesia Stock Exchange (IDX) through various stock indices, one of which is the LQ45 index. The LQ45 Index contains 45 company stocks with high liquidity and good financial fundamentals. In recent years, the movement of the LQ45 index has shown a sharper decline compared to the JCI, leading to a decline in the value of companies listed in the LQ45 index. The factors that affect firm value are financial factors, including ROA, EPS, and firm size, as well as non-financial factors, namely gender diversity and the company’s ESG value. This study aims to determine the influence of ROA, EPS, firm size, gender diversity, and ESG disclosure on firm value in companies listed in the LQ45 stock index for the 2021–2024 period. The data used is secondary data. Sampling was carried out using the purposive sampling technique and twenty-seven company samples were obtained. The data analysis method used is panel data regression analysis. The study’s results indicate that ROA and gender diversity each have a positive and statistically significant partial effect on firm value, whereas firm size, EPS, and ESG disclosure each do not have a statistically significant partial effect on firm value. These findings can serve as a reference for investors in managing their investments and for policymakers in formulating policies to enhance firm value.